INTERMEDIAL INDIAN OCEAN - In Conversation with Harrikrisna Anenden (Workshop Intermedial Indian Ocean - 2021, 2022)
As part of the Indian Ocean events in November 2021, director Harrikrisna Anenden was a guest of the Africa Multiple Cluster of Excellence in Bayreuth. In this interview, he talks with Prof. Dr. Ute Fendler, Deputy Spokesperson of the Cluster, and Jelena Mijajlovic about his film "Draupadi's Veil". The director from Mauritius received his training in Nairobi, Antwerp and London. Harrikrisna has been working as a filmmaker since 2005 and has since then directed both documentaries and feature films across Africa and in India, such as the award-winning feature films The Cathedral (2006) and The Children of Troumaron (2012, co-directed with Sharvan Anenden), which are both based on the writings of the Mauritian author Ananda Devi and portray life in Port-Luis – the capital of Mauritius. His film "Draupadi's Veil" is about a mother's sacrifice to save her son who has come down with a serious case of meningitis.